Pengukuran Kinerja Supply Chain Otak-Otak Bandeng Menggunakan Supply Chain Operation Reference (SCOR) dan Analytical Hierarchy Process (AHP) - Akhmad Wasiur Rizqi; Dhidu Usrin Yadani; Muhammad Syafiqul Ma’arif (JURNAL AGROINDUSTRI HALAL, 2024)
The supply chain is one of the things that plays a role in business continuity. Not only in large-scale industries, a small and medium SME also needs to pay attention to the supply chain so that the business can develop and be sustainable. Supply chain performance measurement needs to be done to measure and evaluate supply chain performance that is currently ongoing. Supply chain operation reference and Analytical Hierarchy Process are used in creating performance measurement models. There are 29 validated Key peformance Indicators to create hierarchical models which are then normalized snorm de boer and AHP in determining weights with Expert choice 11. The measurement of supply chain performance in milkfish SMEs bu afifah obtained 64 meaning average or average with an indicator range between 50-70. In addition, the attribute that has the greatest influence weight is plan with a value of 0.302, then source with a value of 0.246, make with a value of 0.168, deliver with a value of 0.119, return with a value of 0.084 and enable with a value of 0.080